Fitorremediação induzida do chumbo com feijão-de-porco (Canavalia ensiformes (L.) D.C.) - Bighi, Kelly Nery (2016)
This work aimed to analyze the jack beans potential to extract lead from artificially contaminated soil and check the application of EDTA and gibberellin induces greater phytoextraction and analyze the influence of lead in some morphological parameters an